2023
DOI: 10.1186/s12913-023-09874-x
|View full text |Cite
|
Sign up to set email alerts
|

“Building the plane while flying it” Reflections on pandemic preparedness and response; an organisational case study

Karen McKenna,
Stéphane Bouchoucha,
Bernice Redley
et al.

Abstract: Background The COVID-19 pandemic provided a unique opportunity to learn about acute health organisations experiences implementing a pandemic response plan in real-time. This study was conducted to explore organisational leader’s perspectives and experience activating a COVID-19 pandemic response plan in their health service and the impact of this on service provision, clinicians, and consumers. Methods This study was conducted at a large metropolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Staff within the operating suite were the only department in the Health Service to consistently wear surgical masks and eye-protection pre-pandemic. PPE was used periodically in other departments throughout the health service, when caring for patients in transmission-based precautions however, the time spend in PPE would be limited to patient interactions and was not consistent with the prolonged duration of PPE use during the COVID-19 pandemic ( 8 ). A study into factors that influence compliance with PPE use, identified that poor compliance and inconsistent use of PPE has been the main cause of healthcare associated transmission of COVID-19 ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staff within the operating suite were the only department in the Health Service to consistently wear surgical masks and eye-protection pre-pandemic. PPE was used periodically in other departments throughout the health service, when caring for patients in transmission-based precautions however, the time spend in PPE would be limited to patient interactions and was not consistent with the prolonged duration of PPE use during the COVID-19 pandemic ( 8 ). A study into factors that influence compliance with PPE use, identified that poor compliance and inconsistent use of PPE has been the main cause of healthcare associated transmission of COVID-19 ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the increased use of PPE can be seen from the analysis of PPE consumption data, demonstrating that there was an exponential increase in PPE supply and usage. In a 6–12 month period during the pandemic, the use of P2/N95 masks was equivalent to 25 years of pre-pandemic use, and the storage of long-sleeve gowns increased significantly, with a reported 40,000 gowns maintained on-site as a reserve supply ( 8 ). Guidance provided to HCWs during the COVID-19 pandemic on the minimum PPE standard for providing care to patients with suspected or confirmed COVID-19 included: respiratory protection in the form of surgical masks and P2/N95 respirators, long sleeve gowns, eye protection including glasses and face shields, and gloves ( 9 ).…”
Section: Introductionmentioning
confidence: 99%